2020
DOI: 10.3390/land9030090
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Affected Vegetation Dynamics in the Northern Xinjiang of China: Evaluation by SPEI and NDVI

Abstract: Drought and vegetation dynamics in the northern Xinjiang Uygur Autonomous Region of China (NXC), the centre of Asia with arid climate, were assessed using the standardized precipitation evapotranspiration index (SPEI) and the normalized difference vegetation index (NDVI). Analyses were performed through the use of Sen's method and Spearman's correlation to investigate variations in the NDVI and the impacts of drought on vegetation from 1998 to 2015. The severity of droughts in the NXC was assessed by the SPEI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 45 publications
(49 reference statements)
3
40
0
1
Order By: Relevance
“…These results confirm that the climate gradually developed a warmer and more humid pattern in Xinjiang, which confirms previous claims [ 24 , 39 , 53 , 54 , 55 ]. Similar studies have reported a significant wetting tendency in northern Xinjiang [ 4 , 56 ], which is consistent with the trend observed in this study. However, unlike some studies revealed a trend of dryness in Xinjiang from 2000–2015 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirm that the climate gradually developed a warmer and more humid pattern in Xinjiang, which confirms previous claims [ 24 , 39 , 53 , 54 , 55 ]. Similar studies have reported a significant wetting tendency in northern Xinjiang [ 4 , 56 ], which is consistent with the trend observed in this study. However, unlike some studies revealed a trend of dryness in Xinjiang from 2000–2015 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…The vegetation in arid areas could be more sensitive to climate change, which might influence the eco-environment in the countries and regions of the Belt and Road [ 4 ]. The work could enrich the understanding of the effects of climate change on land cover change and vegetation dynamics, laying the basis for its sustainable management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the indices time series for the NDVI, global circulations, precipitation and temperatures meet the basic assumptions of parametric linear analysis, we decided to use the Pearson correlation coefficient (PCC) (Luo et al, 2020) to give a clear picture of the strength of the relationships among them. The preliminary correlation analysis showed that the NDVI vegetation of both March and April, averaged over the entire region, have the highest correlation (0.5 ≤ PCC < 0.8) to the same cumulative amounts of October-March period total precipitation and January-March period mean temperatures according to the seven climate datasets.…”
Section: Pearson Correlation Analysismentioning
confidence: 99%
“…The normalized difference vegetation index (NDVI) (Tucker, 1979), specifically, is the most popular and has been used successfully to detect vegetation and climate conditions interactions worldwide at various temporal and spatial scales (Wu et al, 2015;Xu, Yang & Chen, 2016;Yuan et al, 2019;Luo, Mao, Wen & Liu, 2020). In the study of Luo et al (2020), the dynamic characteristics of drought characterized using the standardized precipitation evapotranspiration index (SPEI) and the NDVI were investigated and evaluated on an interannual scale from 1998 to 2015. Two NDVI datasets were used in the work of Xu et al (2016) to study vegetation growth and its response to climate change reflected by the precipitation, minimum, maximum, and mean temperatures at yearly and monthly time scales from 1982 to 2013.…”
Section: Introductionmentioning
confidence: 99%